2015
DOI: 10.5194/acp-15-13699-2015
|View full text |Cite
|
Sign up to set email alerts
|

Impact of different Asian source regions on the composition of the Asian monsoon anticyclone and of the extratropical lowermost stratosphere

Abstract: Abstract. The impact of different boundary layer source regions in Asia on the chemical composition of the Asian monsoon anticyclone, considering its intraseasonal variability in 2012, is analysed by simulations of the Chemical Lagrangian Model of the Stratosphere (CLaMS) using artificial emission tracers. The horizontal distribution of simulated CO, O3, and artificial emission tracers for India/China are in good agreement with patterns found in satellite measurements of O3 and CO by the Aura Microwave Limb So… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
219
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 114 publications
(243 citation statements)
references
References 61 publications
23
219
1
Order By: Relevance
“…This choice of method is suitable to study the transport of air from the anticyclone, irrespective of where it originated at the surface. The impact of different boundary layer source regions on the Asian monsoon UTLS is an important research topic itself (e.g., Vogel et al, 2015;Tissier and Legras, 2016). The monsoon tropopause is mainly located above 380 K (see Appendix and Fig.…”
Section: Methodsmentioning
confidence: 99%
“…This choice of method is suitable to study the transport of air from the anticyclone, irrespective of where it originated at the surface. The impact of different boundary layer source regions on the Asian monsoon UTLS is an important research topic itself (e.g., Vogel et al, 2015;Tissier and Legras, 2016). The monsoon tropopause is mainly located above 380 K (see Appendix and Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The identification and the relative importance of different transport pathways of tropospheric source gases found within the Asian monsoon anticyclone into the lower stratosphere are the subject of a longstanding debate (Dethof et al, 1999;Park et al, 2004;Randel et al, 2010;Bian et al, 2012;Bourassa et al, 2012;Ploeger et al, 2013;Fairlie et al, 2014;Fromm et al, 2014;Uma et al, 2014;Vogel et al, 2014Vogel et al, , 2015Garny and Randel, 2016;Tissier and Legras, 2016;Orbe et al, 2015). The influence of these different transport pathways on the chemical composition of the extratropical upper troposphere and lower stratosphere (ExUTLS) is important because changes in ozone and water vapor in the ExUTLS have a significant impact on surface climate, even if the perturbation is relatively small.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we use the three-dimensional chemistry transport model CLaMS (McKenna et al, 2002a, b;Pommrich et al, 2014, and references therein) with the setup described in Vogel et al (2015). The simulations covered the time period from May 1 to October 31, 2012, capture the Asian monsoon season in 2012.…”
Section: Clams Simulations With Artificial Air Mass Origin Tracersmentioning
confidence: 99%
“…These different artificial tracers are freshly emitted every 24 h in the boundary layer and their concentrations in the atmosphere 25 represents the airmass contributions from the respective source regions. For more details see Vogel et al (2015Vogel et al ( , 2016. Vogel et al (2015) showed that the emission tracers for India and eastern China are correlated to AURA-MLS (Livesey et al, 2011) satellite measurements of potential vorticity (PV), O 3 , and CO.…”
mentioning
confidence: 99%
See 1 more Smart Citation